Facebook-Augmented Partner Notification in a Cluster of Syphilis Cases in Milwaukee. (January 2014) - Hunter, Paul; Oyervides, Otilio; Grande, Katarina M.; Prater, Daphne; Vann, Vannessa; Reitl, Irmine; Biedrzycki, Paul A.
Public health professionals face many challenges in infectious disease cluster case identification and partner notification (PN), especially in populations using social media as a primary communication venue. We present a method using Facebook and social network diagram illustration to identify, link, and notify individuals in a cluster of syphilis cases in young black men who have sex with men (MSM). Use of Facebook was crucial in identifying two of 55 individuals with syphilis, and the cooperation of socially connected individuals with traditional PN methods yielded a high number of contacts per case. Integration of PN services for HIV and sexually transmitted diseases, as well as collaboration between the city and state information systems, assisted in the cluster investigation. Given that rates of syphilis and HIV infection are increasing significantly in young African American MSM, the use of social media can provide an additional avenue to facilitate case identification and notification.